DEVELOPMENT PROCESS OF WATERSHED PARTNERSHIP: A CASE STUDY OF LIMBOTO WATERSHED - GORONTALO, INDONESIA - Hidayat, Gun Gun; Kakizawa, Hiroaki (Indonesian Journal of Forestry Research, 2014)
Establishment of watershed partnership is required to achieve integrated watershed management in Indonesia. Taking “partnership of Limboto watershed” as a case study, this study aimed to explore the development process of watershed partnership and its state and role in a watershed. Data and information were collected through interviews, group discussions and questionnaire survey. The results showed that in the early stages, through a good preparation process, the partnership gained recognition and support from stakeholders. Informal, open, and voluntary processes were adopted by the coordinator of the partnership for the establishment and initial operation phases which gave the partnership the experience of being inclusive and an active period which was considered as a good success. However, in the next phase, the partnership was unable to cope with the formalization of the watershed partnership as demanded by the decentralized institution by having a new structure without a definite and responsible institution, secretariat and budget source due to lack of interest of the expected local government to take on the responsibility. Formalization resulted in the disfunction of the partnership. Though, many participants considered the partnership had a positive role, especially concerning exchange of information and improvement of concern about the community. This partnership did not yet function for integrated watershed management, but more to educate and inspire people on watershed conservation through project-based activities.